Biofilm-forming microorganisms causing hospital-acquired infections from intravenous catheter: A systematic review - Cangui-Panchi, Sandra Pamela; Ñacato-Toapanta, Anahí Lizbeth; Enríquez-Martínez, Leonardo Joshué; Reyes, Jorge; Garzon-Chavez, Daniel; Machado, António (Current research in microbial sciences, 2022)
•Systematic analysis of 25 studies on biofilm prevalence of nosocomial infections.•Central intravenous catheters promote colonization by biofilm-forming microorganisms.•Several in vitro and in vivo infection models are used to evaluate biofilm formation.•Among 59 and 100% of microorganisms from intravenous catheters established biofilms.•Strategies for antibiofilm agents depends of antimicrobial resistance mechanisms. The high prevalence of nosocomial infections is related to the use of medical insertion devices such as central venous catheters (CVCs). Most of the microorganisms causing nosocomial infections are biofilm producers, this characteristic allows them to adhere to abiotic surfaces and cause initial catheter infections that can lead to bloodstream infections. Our main goal in this systematic review was to evaluate the prevalence of biofilm among CVC-related infections, particularly among Intensive Care Unit (ICU) patients, in the studies applying different in vitro and in vivo methodologies. All studies reporting clinical isolates from patients with catheter-related nosocomial infections and biofilm evaluation published up to 24 June 2022 in the PubMed and Scopus databases were included. Twenty-five studies met the eligibility criteria and were included in this systematic review for analysis. Different methodologies were applied in the assessment of biofilm-forming microorganisms including in vitro assays, catheter-infected in vitro, and in vivo mouse models. The present study showed that between 59 and 100% of clinical isolates were able to form biofilms, and the prevalence rate of biofilm formation varied significantly between studies from different countries and regions. Among the clinical isolates collected in our study set, a wide variety of microorganisms including Gram-positive strains, Gram-negative strains, and Candida albicans were found. Many authors studied resistance mechanisms and genes related to biofilm development and surface adherence properties. In some cases, the studies also evaluated biofilm inhibition assays using various kinds of catheter coatings. [Display omitted]